Metaphor as means of realising the tactics of political insult (in English political discourse) - Sidak, O.O. (Харкiвський нацiональний унiверситет iм. В.Н. Каразiна, 2011)
The article describes metaphoric means of realising the tactics of political insult of the speech strategy of ruining the image of a politician in English publicist discourse. The tactics of political insult is embodied in such varieties as discrediting, disqualification and discrimination. Communicative success of the tactics of political insult depends on achieving humorous effect.
Keywords: speech strategy of ruining the image of a politician; tactics of political insult; metaphor; humorous effect